Fluorescent cannabinoids: Stratagies towards the synthesis of fluorescently labelled CB2 receptor ligands - Yates, Andrew Stephen (2005)
An increased understanding of the peripheral cannabinoid receptor (CB2) is required due to the CB2 receptor's emerging involvement in a number of disease states. New fluorescent technologies are capable of generating information about the CB2 receptor systems that has been unachievable using existing pharmacological methods i.e. radioisotope techniques.